Estructuras adaptables (2009)
The research Project suggests that the current architectural habitat is largely presented in a rigid, static and non- modifiable way, making it impossible to make future transformations. The research Project states that adaptability and transformation are vital components for society, as well as that architecture and design should give answers to current changes. It is here where the mobile systems appears, (which incorporate the feedback concept for its control and movement) and today they are outlined as a more efficient way to produce adaptative answers. For this reason, the research group (GEA) has come exploring and experimenting during the last three years with more than 20 mobile systems, aiming to apply the features of these systems in order to build and develop an adaptable architecture, satisfying the needs of contemporary man, society and the world